Prevalence, incidence, and risk factors for herpes zoster in systemic lupus erythematosus: a systematic review and meta-analysis - Wang, Hong-Fei; Gao, Yan; Lin, Zheng; Liu, Shan; Cao, Yi; Li, Qiu-Shuang (Frontiers in Immunology, 2025)
BackgroundPatients with systemic lupus erythematosus (SLE) are particularly vulnerable to infections, with herpes zoster (HZ) being the most common opportunistic infection. This meta-analysis aimed to systematically review the available literature on the prevalence, incidence, and risk factors of HZ in SLE patients.MethodsA comprehensive search through Embase, PubMed, Web of Science, and Cochrane Library was conducted for studies published up to November 1, 2024. Both observational studies (including cohort, case-control, and cross-sectional) and randomized controlled trials (RCTs) were included, with study types selected according to the specific objectives. Funnel plots and Egger’s test were employed to assess publication bias. Hazard ratios (HRs) and odds ratios (ORs) were converted to relative risks (RRs), and pooled estimates were calculated using a fixed-effect or random-effects model.ResultsA total of 51 studies with 246, 822 SLE patients were included in this meta-analysis. The pooled prevalence and incidence of SLE-HZ were 12.3% (95%CI 10.5-14.1) and 22.0 cases per 1000 person-years (95%CI 17.4-27.9). Glucocorticoids use (RRs=2.83, 95%CI 2.10-3.81), cyclophosphamide use (RRs=2.52, 95%CI 1.60-3.98), mycophenolate mofetil use (RRs=3.00, 95%CI 1.07-8.40), azathioprine use (RRs=1.40, 95%CI 1.18-1.67), anifrolumab use (RRs=2.59, 95%CI 1.52-4.41), having lymphopenia (RRs=2.31, 95%CI 1.54-3.46), and the presence of comorbid conditions such as renal involvement (RRs= 1.80, 95%CI 1.34-2.42) were identified to increase the risk of HZ in SLE patients.ConclusionThe existing evidence highlights the both high prevalence and incidence of HZ in SLE patients. By identifying risk factors associated with the development of HZ in SLE patients, optimization of management strategies and treatment choices can be achieved. Concurrently, physicians could be better equipped to choose patients who would most likely gain from the HZ vaccine.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024331310, identifier CRD42024331310.